Analisis Sensitivitas Metode AHP dalam Penentuan Guru Teladan Berdasarkan Kinerja - Sitompul, Weny Grace; Nababan, Esther Sorta Mauli; Gultom, Parapat; Sawaluddin, Sawaluddin (MES: Journal of Mathematics Education and Science, 2024)
The aim of this research is to examine the final ranking results of the AHP method through sensitivity analysis. The sensitivity value is sought to predict the situation if there is a change in the weight of the decision criteria. A case example in this research is the determination of an exemplary teacher at SDN 028068 Binjai based on their performance using the AHP method. The decision criteria for this research are Academic Qualifications ( ), Educator Certificate ( ), Pedagogical Competency ( ), Personality Competency ( ), Social Competency ( ), and Professional Competency ( ). Before sensitivity analysis, preliminary final results were obtained by the AHP method. From the final results of the initial ranking using the AHP method, experiments were carried out through several stages of sensitivity analysis. Of all the experiments, generally experienced the most changes in priority order, especially in  with 12 changes in alternative priority order. Then through the sensitivity testing process, sensitivity 1 gets the highest value in the experiment with a value of 0.0282, sensitivity 2 in the experiment with a value of 0.1269, and sensitivity 3 in the  experiment with a value of 0.1256.